Groundwater Quality Assessment for Irrigation: Case Study in the Blinaja River Basin, Kosovo - Hazir S. Çadraku (Salehan Institute of Higher Education, 2021)
Groundwater is an important source for a drink and irrigation in the Blinaja river basin. Understanding knowledge of irrigation water quality is critical to the management of water for long-term productivity. Historically for this study area there is no data and information regarding the quality and use of water for irrigation needs. Therefore, there was a need to assess water quality based on data analysed from eight sampling points. The purpose of this paper is to evaluate, relying on analytical results, the quality of groundwater in the Blinaja river basin for the purpose of its use for irrigation of agricultural crops. For this purpose, in the Blinaja River Basin in different months during 2015, 2016, 2018 and 2019, 28 water samples were taken to assess the quality of groundwater for irrigation. Water samples were analysed in a laboratory for some of the key quality indicators; pH, EC, hardness (TH), Ca, Mg, Na, K, HCO3, SO4, Cl, etc. and then irrigation water quality indices were calculated such as: percentage of Na (% Na), SAR (Sodium Adsorption Ratio), PI (Permeability index), KR (Kelly's ratio), etc. The overall objective of this study was to assess the quality of water to be used by the inhabitants of the area for irrigation of agricultural crops. Analytical procedures for the laboratory determinations of water quality have been given in several publications (USDA Handbook 60 by Richards, 1954; FAO Soils Bulletin 10 by Dewis and Freitas1970; APHA 2005). Doi: 10.28991/cej-2021-03091740 Full Text: PDF